ChemInform Abstract: Liquid‐Phase Synthesis of Ba2V2O7 Phosphor Powders and Films Using Immiscible Biphasic Organic—Aqueous Systems. Issue 41 (September 2016) - Takahashi, Mami; Hagiwara, Manabu; Fujihara, Shinobu
Abstract: Both powders and films of the title phosphor are synthesized using a biphasic organic—aqueous system consisting of an aqueous solution of Ba(OAc)2 and a solution of VO(OEt)3 in xylene (80 °C, 24 h).